The position of the Soviet Union, the United States of America, and Iran, towards Britain's withdrawal from the Persian Gulf region (1968-1971(. (Journal of Misan Researches, 2023)
In 1968, Britain announced its decision to withdraw from the Arab Gulf region, provided that it actually took place in 1971, and the Soviet Union sought to intervene and play a key role in this aspect, and at the same time, Iran was very cautious about any planning by the Soviet Union to expand in the region. Following the announcement of the British withdrawal, especially after the increase in the activity of the Soviet Union represented in the strengthening of relations between it and the countries of the region, such as its stance towards the Iraqi-Kuwaiti crisis in 1961 AD, and the establishment of diplomatic relations between the Kuwaiti and Soviet sides in 1963 AD, as well as other relations in various fields, and documenting its presence in the Gulf region In the Arab world, the Soviet Union was able to establish sea routes through Iran, in addition to obtaining facilities for air transportation from Iran and Bahrain.For its part, the United States of America was keen to protect its interests in the Persian Gulf and to keep the Soviet Union away from it; Therefore, she studied the subject of reliance on the Kingdom of Saudi Arabia and Iran; To play the role of the regional power that will protect the security and stability of the region.In turn, Iran tried to win the position of the Kingdom and cooperate with it, but the Iranian demands in Bahrain and the three islands (Tunb al-Kubra, Tunb al-Sughra, and Abu Musa) affected the position of the Kingdom and the rest of the region's countries towards Iran